Π‐Conjugated Polymers Incorporating a Novel Planar Quinoid Building Block with Extended Delocalization and High Charge Carrier Mobility. Issue 22 (23rd April 2018) - Kim, Yunseul; Hwang, Hansu; Kim, Nam‐Koo; Hwang, Kyoungtae; Park, Jong‐Jin; Shin, Ga‐In; Kim, Dong‐Yu
Abstract: Two novel conjugated polymers incorporating quinoidal thiophene are successfully synthesized. By combining 1D nuclear magnetic resonance (NMR) and 2D nuclear Overhauser effect spectroscopy analyses, the isomeric form of the major quinoid monomer is clearly identified as the asymmetric Z, E ‐configuration. The quinoidal polymers are synthesized via Stille polymerization with thiophene or bithiophene. Both quinoidal polymers exhibit the low band gap of 1.45 eV and amphoteric redox behavior, indicating extended conjugation owing to the quinoidal backbone. These quinoidal polymers show ambipolar behaviors with high charge carrier mobilities when applied in organic field‐effect transistors. In addition, the radial alignment of polymer chains achieved by off‐center spin‐coating leads to further improvement of device performance, with poly(quinoidal thiophene–bithiophene) exhibiting a high hole mobility of 8.09 cm 2 V −1 s −1, which is the highest value among the quinoidal polymers up to now. Microstructural alteration via thermal annealing or off‐center spin‐coating is found to beneficially affect charge transport. The enhancement of crystallinity with strong π–π interactions and the nanofibrillar structure arising from planar well‐delocalized quinoid units is considered to be responsible for the high charge carrier mobility. Abstract : Quinoidal conjugated polymers incorporating a novel quinoid building block are synthesized via short four steps. The highly planar and well‐delocalized quinoidal structure induces strong π–π interaction between polymer chains. High hole mobilities of 8.09 and 4.82 cm 2 V −1 s −1 are achieved for poly(quinoidal thiophene–bithiophene) and poly(quinoidal thiophene–thiophene), respectively, when applied in organic field‐effect transistors prepared by off‐center spin‐coating.